Weed Dynamics, Growth, and Yield of Groundnut (Arachis hypogaea L.) as Influenced by Variety and Plant Population - Shittu, Emmanuel Abraham; Bello, Tasiu Tukur; Attah, Abu Daniel (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Field trials were conducted during the 2023 rainy season at Bayero University Kano (BUK) and Minjibir to evaluate the effects of groundnut variety and plant population on weed dynamics, crop growth, and yield. The experiment followed a 5 × 3 factorial arrangement, comprising five groundnut varieties of four improved (SAMNUT-21, SAMNUT-23, SAMNUT-24, SAMNUT-27) and one local (Maibargo) and three plant populations (15,000,000, 22,500,000, and 30,000,000 plants ha⁻¹). Treatments were laid out in a randomized complete block design (RCBD) with three replications. Soil analysis revealed contrasting characteristics between locations: BUK had predominantly loamy sand (86% sand) with relatively higher calcium content (Ca²⁺ = 5.8 cmol kg⁻¹), while Minjibir’s soil, a sandy loam with higher clay content (8.8%), contained greater levels of micronutrients such as iron (Fe = 212.59 ppm). Significant (p < 0.05) varietal effects on weed morphology were observed at Minjibir, where SAMNUT-24 and Maibargo suppressed broadleaf weeds, and SAMNUT-23 and SAMNUT-24 reduced sedge density. Plant population had a highly significant effect (p < 0.001) on broadleaf and grass weed suppression at both sites, with the highest density (30,000,000 plants ha⁻¹, corresponding to 30 cm spacing) showing the greatest suppression. Growth traits varied among varieties, with SAMNUT-21 exhibiting the tallest plants (8.1 cm) and Maibargo producing the highest dry matter (68.7 g). SAMNUT-23 recorded the highest pod and kernel yields at both BUK (1013.7 and 599.7 kg ha⁻¹) and Minjibir (639.6 and 363.9 kg ha⁻¹). Although higher plant densities enhanced weed suppression, they reduced yield due to intra-species competition. The optimal pod and kernel yield at BUK (570.4 and 334.2 kg ha⁻¹) was achieved at the lowest density (15,000,000 plants ha⁻¹).